Effect of spironolactone use in pulmonary arterial hypertension – analysis from pivotal trial databases - Zeenat Safdar (SAGE Publishing, 2021)
Spironolactone, a common diuretic used in the treatment of pulmonary arterial hypertension (PAH), improves cardiopulmonary hemodynamics by attenuating the adverse effects of hyperaldosteronism on endothelin type-B receptor function within pulmonary endothelial cells. Spironolactone has demonstrated vascular remodeling properties and reduced all-cause mortality in patients with severe heart failure. Despite widespread use, however, its effect on morbidity and mortality in PAH has not been fully explored. A large cohort of PAH patients from a harmonized dataset from four pivotal trials were analyzed to characterize the patient population and outcomes associated with spironolactone treatment. Of 1229 evaluable patients, 74% were female, mean age of 47 ± 15 years, baseline six-minute walk distance (6MWD) 345 ± 74 m and 75% were World health Organization (WHO) functional class (FC) III/IV. Of the patients receiving spironolactone, 43% were on subcutaneous treprostinil, compared to 29.9% of those patients who were not receiving spironolactone. Long-term spironolactone-treated PAH patients were older (p = 0.01), had lower baseline 6MWD (p = 0.01) and cardiac index (p < 0.01), higher baseline Borg dyspnea score (p = 0.01), WHO functional class, and right arterial pressure (p < 0.01). Additionally, spironolactone-treated patients tended to have higher hazard of clinical worsening (p < 0.01). A propensity analysis was performed and when controlled for disease severity, revealed that spironolactone-treated patients did not demonstrate improved outcomes in terms of survival and clinical worsening. Across studies, the current analysis has demonstrated that the actions of spironolactone within the context of the PAH disease process may differ from its action in CHF patients. Despite reported outcomes of spironolactone use in patients with left heart disease, these findings may not translate to right heart failure and pulmonary vascular pathology, as similar outcomes have not necessarily been recognized in the PAH patient population. Future studies are needed to explore these findings further.